MENANAMKAN PENDIDIKAN KARAKTER MELALUI SEJARAH HIDUP HAJJAH RANGKAYO RASUNA SAID - Junita Sari; Anny Wahyuni; Budi Purnomo (UNZAH Genggong, 2021)
Hajjah Rangkayo Rasuna Said is an Indonesian national hero from West Sumatra. From 1926 to 1965, she played a role in fighting for the rights of Indonesian women. This study aims to determine: (1) the background of Rasuna Said's life, (2) Rusuna Said's struggle in 1926-1965, (3) the character value of Rasuna Said as a role model for the millennial generation. This study uses the Kuntowijoyo historical research method which includes five stages, namely (1) topic selection, (2) source collection (heuristics), (3) source criticism (verification), (4) interpretation (interpretation), (5) historical writing ( History). The results of this study are (1) Background in life: HR Rasuna Said is a rich man of Minang blood. His father Haji Muhammad Said is a businessman and former activist. (2) As for the struggles carried out by Rasuna Said, starting from becoming a teacher, participating in various organizations, being jailed for spreek delict, to becoming a magazine writer, and a career in the Indonesian parliament to fight for the fate of women and their nation. (3) HR Rasuna Said is a figure of a woman and a hero who we can study or exemplify through two aspects, namely: exemplary and heroism. Exemplary aspects can be seen from the figure of HR Rasuna Said, who is a woman who is smart, has noble character, is persistent and tough, and has a very good understanding of religion and politics. From her heroic aspect, HR Rasuna Said is a woman who is brave, willing to sacrifice, and loyal to her homeland, namely Indonesia. Rasuna Said's HR trait is still very relevant to be imitated by the Millennial generation. Keywords: heroine, Hajjah Rangkayo Rasuna Said, exemplary value.